Analisis Kritik Sastra Objektif Pada Puisi Hujan Bulan Juni - Henry Wintoro Lubis (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the poem “Hujan Bulan Juni” by Sapardi Djoko Damono using an objective literary criticism approach. This approach views literary works as autonomous structures whose meanings can be understood through intrinsic elements without considering the author’s background or readers’ responses. The research employs a qualitative descriptive method, with data collected through library research and close reading of the poem. Data analysis focuses on intrinsic elements, including theme, diction, imagery, figurative language, and poetic structure. The findings reveal that “Hujan Bulan Juni” constructs its meaning through the coherence of its intrinsic elements. The theme of sincerity and patience is implicitly conveyed through symbolic diction, personification, and consistent natural imagery. Therefore, this study demonstrates that the poem’s meaning can be objectively interpreted through textual analysis, confirming the relevance of objective literary criticism in the study of Indonesian poetry.